Eyes of identification: challenges and opportunities in leveraging highly visible, multiple-level histories - Debra Rosser; Shurlee Swain (Scottish Journal of Residential Child Care)
Histories of out of home 'care' have traditionally fallen into four categories: in-house productions, commissioned histories; academic studies and survivor narratives. Each of these is problematic. A more inclusive approach, which encourages a close relationship between historian and those who lived the experience, is offered through projects arising from Australian government enquiries into indigenous, migrant and Australian-born children in care. These projects challenge historians on two main fronts: They defy historians' 'scholarly distance' and require them to embrace alternative, often competing and personally confronting, histories as they seek to incorporate care leavers' voices in published history. A greater challenge, though, is for historians to find effective ways to intersect public history with public policy so that the undesirable legacies of the past do not recur in the futures of the children who are in out of home care today.